Application of Data Quantitative Analysis in the Diagnosis of Satellite Attitude and Orbit Control System Health Status - Qian, Fangliang; Zhang, Lei; Xiang, Kun; Nie, Zhanghai; Meng, Qichen
Relying on the organic organization and cooperation of the multifunctional organs in the body, the organism completes the basic form of life. Attitude Orbit Control System of Satellite (AOCS) is composed of multiple sensors and actuators. It is effectively organized and processed by the on-board computer to complete the attitude and orbit control tasks of the satellite platform. This article compares AOCS to "organisms" that require long-term health diagnosis and treatment and organically decomposes their nominal functional blocks. Then an AOCS quantitative health assessment method is proposed that the health quantitative diagnosis system designed based on. And it can calculate the satellite AOCS quantitative health status score to support the maintenance of the on-orbit satellite AOCS efficiently.